The anthropology of Donald Trump
1 online resource.
Keywords: "The Anthropology of Donald Trump is an edited volume of original anthropological essays, composed by some of the leading figures in the discipline. It applies their concepts, perspectives, and methods to a sustained and diverse understanding Trump's supporters, policies, and performance in office. The volume includes ethnographic case studies of 'Trump country', examines Trump's actions in office, and moves beyond Trump as an individual political figure to consider larger structural and institutional issues. Providing a unique and valuable perspective on the Trump phenomenon, it will be of interest to anthropologists and other social scientists concerned with contemporary American society and politics as well as suitable reading for courses on political anthropology and U.S. culture"--